2020
DOI: 10.1016/j.joms.2020.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Marsupialization of Mandibular Cysts in Improving the Healing of Related Bone Defects

Abstract: Purpose: Marsupialization, designed to reduce the mandibular cyst volume, has continued to debated regarding its influence on the healing of the related bone cavity. The aim of the present study was to evaluate the 3-dimensional radiographic variation over time in mandibular odontogenic cystic lesions after marsupialization and assess the correlations between these variations and variables that can affect the procedure. Materials and Methods: We planned a retrospective cohort study. The predictor variables wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 38 publications
5
19
0
Order By: Relevance
“…[ 8 ] The total decrease in the volume of the cystic cavity is correlated with the duration of decompression. [ 12 13 ] Marker et al . [ 14 ] reported that at least 12 months is needed for a reduced rate of 50%–60% in cystic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] The total decrease in the volume of the cystic cavity is correlated with the duration of decompression. [ 12 13 ] Marker et al . [ 14 ] reported that at least 12 months is needed for a reduced rate of 50%–60% in cystic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Volume reduction and changes in the bone quality during decompression procedures can be successfully monitored and predicted with a three-dimensional CT evaluation. [ 8 13 ] Shudou et al . [ 21 ] reported that the future shape of marsupialized odontogenic keratocysts can be predicted with significant accuracy with computerized tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the jaw bone starts to remodel over a long period of time, causing a reduction in cystic volume to the extent of permitting it to enucleate or to leave it to heal completely [2,12]. This article was previously presented as an abstract on the Authorea website (10.22541/au.165494343.36193429/v10).…”
Section: Introductionmentioning
confidence: 99%
“…Since many lesions have similar radiologic features, differentiation based on radiological appearance alone is not possible; therefore, biopsy is required in addition to clinical examination for final diagnosis [2]. The type of cyst significantly influences therapy, but both complete enucleation of the cyst (cystectomy) and marsupialization to the oral cavity (cystostomy) require radiological follow-up in some cases over many years to assess the extent of the bony lesion or neo-ossification [3,4].…”
Section: Introductionmentioning
confidence: 99%